2021
DOI: 10.1371/journal.pone.0259367
|View full text |Cite
|
Sign up to set email alerts
|

Comparable performance on a spatial memory task in data collected in the lab and online

Abstract: Online data collection offers a wide range of benefits including access to larger and more diverse populations, together with a reduction in the experiment cycle. Here we compare performance in a spatial memory task, in which participants had to estimate object locations following viewpoint shifts, using data from a controlled lab-based setting and from an unsupervised online sample. We found that the data collected in a conventional laboratory setting and those collected online produced very similar results, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 35 publications
(44 reference statements)
4
13
0
Order By: Relevance
“…This virtual study allowed us to recruit a large and diverse sample of participants from across the globe, and we used selfreported assessments to explore multiple cognitive domains relating to hippocampal functioning in a quick and accessible way. Although self-reports do not always correspond well to objective measures of cognition [58,59], physical tasks tend to be less impacted by metacognitive inaccuracies than cognitive tasks [60] and the self-reported assessments used here show good corresponded with objective measures [15,52,61]. Furthermore, when it comes to Alzheimer's and related dementias, subjective memory complaints are often used as an early indicator of increased risk, even in the absence of overt memory impairment [27].…”
Section: Plos Onementioning
confidence: 77%
“…This virtual study allowed us to recruit a large and diverse sample of participants from across the globe, and we used selfreported assessments to explore multiple cognitive domains relating to hippocampal functioning in a quick and accessible way. Although self-reports do not always correspond well to objective measures of cognition [58,59], physical tasks tend to be less impacted by metacognitive inaccuracies than cognitive tasks [60] and the self-reported assessments used here show good corresponded with objective measures [15,52,61]. Furthermore, when it comes to Alzheimer's and related dementias, subjective memory complaints are often used as an early indicator of increased risk, even in the absence of overt memory impairment [27].…”
Section: Plos Onementioning
confidence: 77%
“…Firstly, we used online data collection, but to minimize the effect of possible noise, we oversampled our subject pool to one-hundred participants, whereas typical IAT studies use smaller sample sizes [35]. Moreover, there is evidence of similar results obtained from both online and in-lab studies [36]. We also checked for outliers in our data (e.g., higher percentage of errors or longer time for experiment completion, compared to the total sample), and none were found, therefore, the data of all participants were included in the data analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this explanation, previous research suggests that adjustments require time and cognitive effort (Epley et al, 2004 ) and as a result, individuals often stop adjusting their responses once a plausible estimate is reached thereby biasing their responses in the direction of the initial anchor (Quattrone, 1982 ; Tversky & Kahneman, 1974 ). If participants in our previous studies (Segen et al, 2022 ; Segen et al, 2021a ) also showed insufficient adjustments, this would explain the systematic bias in the direction of the perspective shift.…”
mentioning
confidence: 81%
“…In our previous work (Segen et al, 2022 ; Segen et al, 2021a ; Segen et al, 2021b ), participants may have used the egocentric self-to-object vector as an anchor for their response, which would result in participants “dragging” the object with them following a perspective shift. In line with this explanation, previous research suggests that adjustments require time and cognitive effort (Epley et al, 2004 ) and as a result, individuals often stop adjusting their responses once a plausible estimate is reached thereby biasing their responses in the direction of the initial anchor (Quattrone, 1982 ; Tversky & Kahneman, 1974 ).…”
mentioning
confidence: 98%
See 1 more Smart Citation